Hypoxia and oxidative stress in breast cancer. Hypoxia and tumourigenesis - Knowles, H; Harris, A (BioMed Central, 2001)
The microenvironmental hypoxia that arises as a consequence of the development of a solid tumour also acts to promote tumour growth. Hypoxia induces the expression of key components of the angiogenic and apoptotic signalling cascades, the glycolptic pathway and various cell-cycle control proteins. At the cellular level it mediates the infiltration and accumulation of tumour-associated macrophages within avascular tumour regions. Complex interactions between tumour cell and macrophage hypoxia-regulated gene products and their associated pathways form the basis for the hypoxic promotion of tumourigenesis and malignant progression.